Types of Sentences Used by Male and Female Writers in Journal Article Abstracts - Willem Saragih; Christine Helena Natalia (BAHAS, 2020)
ABSTRACTThis study analyzed the types of sentences used in the Abstracts of Journal Articles written by 10 Female and 10 Male fully sourced from the Book Program of The First Annual International Seminar UNIMED Medan: November 19, 2016. Of the 195 sentences, 102 of which were written by females, and 92 by Males, all types of sentences are present. The occurrence of the types of sentence used by Females is Simple Sentence (50.1%), Complex Sentence (37.1%), Complex - Compound Sentence (6.8%), and Compound Sentence (4.9%). By Males , Simple Sentence is (50.%), Complex Sentence (41%), Compound Sentence (5.4%) and Complex- Compound Sentence (3.3%). Thus, this proves that the frequency is only different in Complex-Compound, i.e. by Females in the third place, but by Males in the fourth and Compound in the third. Overall, it can be concluded that gender has no relation with sentence types.Key Words: Types of sentence; Female and Male; Abstracts